Chemotherapy for low-grade glioma: when, for whom, which regimen?. Issue 6 (December 2015) - van den Bent, Martin J.
Abstract : Purpose of review: The role of chemotherapy in low-grade glioma has been redefined with the long-term follow-up of the RTOG 9802, which investigated adjuvant procarbazine, CCNU, and vincristine (PCV) chemotherapy in addition to radiotherapy, and the results of EORTC trial 22033 in a similar patient population that compared temozolomide to radiotherapy. Recent findings: RTOG 9802 trial showed an increase in overall survival after adjuvant chemotherapy. Median overall survival increased from 7.8 to 13.3 years, with a hazard ratio of death of 0.59 (log rank: P  = 0.002), and despite a 77% cross-over rate to chemotherapy in patients progressing after radiotherapy. The EORTC trial 22033 did not reveal differences in progression-free survival between patients treated initially with radiotherapy or with temozolomide. Summary: With these results and similar results of trials in anaplastic glioma, radiotheraphy with PCV is now to be considered standard of care for low-grade glioma requiring postsurgical adjuvant treatment. The optimal parameter for selecting patients for adjuvant PCV has not yet been fully elucidated. It is still unclear if temozolomide can replace PCV, but temozolomide is better tolerated than nitrosoureas. The current evidence supports treating patients with grade II and III glioma based on their molecular characteristics.